STUDYING THE EFFECTIVENESS OF TREATMENT WITH REMOVABLE PROTESES FOR TOOTH-RELATED ELDERLY PATIENTS - Matrizayeva Gulmira Ne'matjon qizi; Omonova Dilnura Ulugbek qizi (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Relevance of the research. The relevance of this research stems from the urgent demographic shift in Uzbekistan, where 23% of the population will be over 60 by 2030 (WHO 2022), creating unprecedented demand for age-appropriate dental prosthetics. The study specifically addresses critical gaps in Khorezm region, which faces severe healthcare disparities with only 4.2 dentists per 10,000 population compared to the 7.1 national  average.  This  research  provides  the  first  comprehensive  evaluation  of removable  prostheses  for  elderly  patients  in  Central  Asia,  where  evidence-based guidelines are currently lacking. Traditional acrylic prostheses show particularly poor outcomes  in  geriatric  populations,  with  37%  developing  stomatitis  due  to  atrophic mucosal changes and declining manual dexterity compromising hygiene. Our study uniquely  examines  both  clinical  outcomes  and  socioeconomic  factors  influencing prosthetic  success  in  resource-limited  settings.  The  findings  will  directly  inform national  geriatric  oral  health  policies,  dental  education  reforms,  and  public  health resource  allocation.  By  comparing  conventional  acrylic  versus  flexible  RPDs,  we address three fundamental gaps: material efficacy in  aging physiology, cost-benefit analysis in low-resource regions, and age-specific treatment modifications. This work aligns with UN Sustainable Development Goal 3 (Good Health) and WHO's 2023 Oral Health  Strategy  for  Aging  Populations,  while  establishing  the  first  evidence-based framework  for  prosthetic  selection  in  Central  Asian  elderly  patients.  The  research outcomes will reduce iatrogenic complications, optimize limited healthcare resources, and improve quality of life for the region's rapidly growing elderly population facing partial edentulism.